Experimental Heat Transfer Study on Green Roofs in a Semiarid Climate during Summer. (18th January 2015) - Issa, Roy J.; Leitch, Kenneth; Chang, Byungik
Abstract : An experimental study was conducted on green roofs under the semiarid summer climatic conditions of West Texas to investigate the effect of soil type, moisture content, and the presence of a top soil grass layer on the conductive heat transfer through the roof. Two soil types were investigated: uniform sand and local silt clay. Tests were also conducted on a control roof. A dual-needle heat-pulse sensor was used to conduct thermal property tests on the soils. The tests reveal that unlike sand, the thermal conductivity of silt clay did not increase continuously with soil moisture. Better heat transfer conditions were achieved when the sand and silt clay roofs were watered to a water depth of 10 mm per day rather than double the amount of 20 mm per day. The roof with silt clay soil had the lowest fluctuation in inner temperature between daytime and nighttime. Green roofs with silt clay soil required more than twice the amount of soil moisture than green roofs with sand to achieve similar roof heat transfer rates. The best net heat flux gains for vegetated green roofs were 4.7 W/m 2 for the sand roof and 7.8 W/m 2 for the silt clay roof.